2015
DOI: 10.1158/0008-5472.can-14-2959
|View full text |Cite
|
Sign up to set email alerts
|

ErbB3–ErbB2 Complexes as a Therapeutic Target in a Subset of Wild-type BRAF/NRAS Cutaneous Melanomas

Abstract: The treatment options remain limited for melanoma patients who are wild-type for both BRAF and NRAS (WT/WT). We demonstrate that a subgroup of WT/WT melanomas display high basal phosphorylation of ErbB3 that is associated with autocrine production of the ErbB3 ligand, neuregulin-1 (NRG1). In WT/WT melanoma cells displaying high levels of phospho-ErbB3, knockdown of NRG1 reduced cell viability and was associated with decreased phosphorylation of ErbB3, its co-receptor ErbB2 and its downstream target, AKT. Simil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…However, concurrent expression of ErbB3 and NRG1 may exist in a subset of human metastatic melanomas (36), and, in these tumors, direct targeting of ErbB3/ErbB2 may be efficacious (37). In other studies, we have identified a subset of wildtype BRAF/wild-type NRAS (neuroblastoma rat sarcoma viral oncogene homolog) melanomas that express both NRG1 and ErbB3 and are dependent on NRG1-ErbB3 signaling for growth (38). Despite the well characterized paradoxical signaling effects of first-generation RAF inhibitors (25,39), RAF inhibitors do not further promote NRG1 expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 91%
“…However, concurrent expression of ErbB3 and NRG1 may exist in a subset of human metastatic melanomas (36), and, in these tumors, direct targeting of ErbB3/ErbB2 may be efficacious (37). In other studies, we have identified a subset of wildtype BRAF/wild-type NRAS (neuroblastoma rat sarcoma viral oncogene homolog) melanomas that express both NRG1 and ErbB3 and are dependent on NRG1-ErbB3 signaling for growth (38). Despite the well characterized paradoxical signaling effects of first-generation RAF inhibitors (25,39), RAF inhibitors do not further promote NRG1 expression in fibroblasts.…”
Section: Discussionmentioning
confidence: 91%
“…In breast and stomach cancers, high ERBB2 levels are associated with rapid tumor growth and metastatic spread and provide the rationale for targeting ERBB2 by treatment with trastuzumab and lapatinib . In a preclinical study of wild‐type BRAF/NRAS but ERBB2‐positive melanoma cell xenografts, it was demonstrated that ERBB2 dimerized with ERBB3, and tumor growth could be reduced significantly in vivo with the ERBB2‐specific antibody pertuzumab …”
Section: Resultsmentioning
confidence: 99%
“…46,47 In a preclinical study of wild-type BRAF/ NRAS but ERBB2-positive melanoma cell xenografts, it was demonstrated that ERBB2 dimerized with ERBB3, and tumor growth could be reduced significantly in vivo with the ERBB2-specific antibody pertuzumab. 48 KIT can be targeted by small-molecule inhibitors, such as imatinib, which are approved for the treatment of gastrointestinal sarcomas with mutations in exon 11, encompassing the juxtamembrane region with amino acids 550 through 591. 49 Melanoma patients with mutated KIT also might benefit from imatinib, but this was not confirmed for patients with amplified KIT.…”
Section: Resultsmentioning
confidence: 99%
“…ErbB3 primarily activates the PI3K/Akt pathway and ErbB2 favors the MAP kinase pathway (Yarden and Sliwkowski, 2001 ). Activation of the ErbB2/ErbB3 signaling unit via overexpression of the receptors, gain-of-function oncogenic mutations, or autocrine release of the ErbB3 ligand, heregulin, have been identified in many types of cancer (Holbro et al, 2003 ; Wolf-Yadlin et al, 2006 ; Sheng et al, 2010 ; Jaiswal et al, 2013 ; Capparelli et al, 2015 ). Given the potency of this interaction, normal cells must maintain tight control over ErbB2/ErbB3 interactions.…”
Section: Discussionmentioning
confidence: 99%